Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s00204-016-1769-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic damage in humans exposed to extremely low-frequency electromagnetic fields

Abstract: The classification of extremely low-frequency magnetic fields by the International Agency for Research on Cancer in the group of 'possible human carcinogens' (group 2B) is essentially based on epidemiologic evidence showing an association between MF exposures and childhood leukaemia. Despite many in vitro and in vivo investigations, there is no established causal relationship yet. However, human cytogenetic biomonitoring studies that were conducted in the past show predominantly positive results, i.e. increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 40 publications
(60 reference statements)
0
11
0
1
Order By: Relevance
“…However, epidemiology studies reported that EMF might in relation to brain cancer and leukemia 5456 . Despite many in vitro and in vivo investigations, there is no established causal relationship yet.…”
Section: Discussionmentioning
confidence: 99%
“…However, epidemiology studies reported that EMF might in relation to brain cancer and leukemia 5456 . Despite many in vitro and in vivo investigations, there is no established causal relationship yet.…”
Section: Discussionmentioning
confidence: 99%
“…It was speculated that exposure to chromium, nickel and/or other metals may lead to the different results between theirs and other investigations. A tendency of DNA damage induced by ELF-EMFs could potentially result in mutagenesis [ 24 ]. The subjects in this study were occupationally exposed to ELF-EMF for more than 20 years, therefore the elevated levels of urinary 8-OHdG and F2-isoprostane observed may be a cumulative effect.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been theorized that these fields may enhance such damage from other sources, e.g. endogenous radicals [26]. Furthermore, the inconclusive nature of laboratory experiments turns this concern more conflicting.…”
Section: The Genotoxic Potential Of Magnetic Fieldsmentioning
confidence: 99%
“…Three important reviews published in the 90s [6,34,35] and recently by Maes and Verschaeve [26], concluded that ELF-EMFs do not directly cause genotoxic effects. Only a small minority of the reported studies indicate potential of these fields to cause genetic changes in biological systems.…”
Section: The Genotoxic Potential Of Magnetic Fieldsmentioning
confidence: 99%